Mendelian Randomisation: Concepts, Opportunities, Challenges, and Future Directions - Sophie C. de Ruiter; Lena Tschiderer; Diederick E. Grobbee; Peter Willeit; Hester M. den Ruijter; A. Floriaan Schmidt; Sanne A. E. Peters (Global Heart)
Mendelian randomisation is an approach in genetic epidemiology that uses genetic variants as instrumental variables to investigate the causal relationship between genetically proxied exposures and health outcomes. During the last years, the number of published Mendelian randomisation studies increased tremendously. There are several opportunities of Mendelian randomisation including obtaining potential causal relationships between both exogenous and endogenous exposures and outcomes and for identifying and prioritising drug-targets to inform clinical trials. However, it is also important to be aware of its challenges. This includes the reliability of results under the assumptions on instrumental variables, being aware of potential biases, the correct and critical interpretation of findings and comparison to the results of randomised controlled trials, as well as the availability of genetic data on specific subgroups. This review provides a comprehensive overview of the opportunities and challenges of Mendelian randomisation and presents key future perspectives.